Leadership in Surgery - Kibbe, Melina R.; Chen, Herbert (Success in Academic Surgery,, 2015)
This comprehensive book teaches the theories and concepts behind leadership and explains the skills and traits needed to become a good leader. The authors discuss practical management skills, including conflict resolution techniques, how to manage difficult personalities and how to effectively manage up. The readers will learn to build and motivate a team, understand personality types and how to manage to their strengths.   Success in Academic Surgery: Leadership in Surgery is a highly useful book to anyone in the surgical field, providing clear examples and useful tips for what to do in the role of a surgical leader from current leaders in surgery.